A dynamic model of optimal reduction of marine oil pollution. (29th October 2004) - Deissenberg, Christophe; Gottinger, Hans; Gurman, Vladimir; Marinushkin, Dmitry
This paper proposes a system of dynamic models to describe the interactive behaviour of different agents (polluters, inspectors, and a principal pollution control agency) involved in the processes of marine oil pollution and of its prevention and purification, under some realistic assumptions. In particular, short- and long-term economic responses of polluters to monitoring efforts, as well as possible collusions between polluters and inspectors, are taken into account. A numerical example is considered using the results of Deissenberg et al., (2001a), which show the existence of optimal fines and inspector wage rates that minimise (along with other variables) a simple and visual "social damage" criterion.